Measuring intellectual capital trends in positivism research: a literature review - Ahmad Nuryaddin, Zayyan (Journal of Multiperspectives on Accounting Literature, 2025)
Purpose: This article aims to see how diverse intellectual capital measurements are in positivist (quantitative) research in 2023. Methodology/approach: This article resulted in literature rivew on the topic of quantitative research on Intellectual Capital on Scopus Q1 Indexed Journals i.e. Journal of Intellectual Capital in 2023 Findings: The finding of this article is that there are three contexts of the topic Intellectual Capital that will be studied in 2023 are Intellectual Capital Conventional Green Intellectual Capital and Intellectual Capital Disclosure. In addition, there is a dominance of topics Intellectual Capital conventional compared to the other two topics Practical implications: The implications of this article can be used as an additional insight literature review Regarding the trend of quantitative research on intellectual capital. Originality/value: The novelty of this research lies in the diversification of intellectual capital measurements in quantitative research.